Isu Laut Tiongkok Selatan: Negara-negara ASEAN Terbelah Menghadapi Tiongkok - Arief Bakhtiar Darmawan; Lady Mahendra (Global Strategis, 2018)
This paper aims to analyze the strategies of each ASEAN member states towards China related to the dispute in the South China Sea (SCS). SCS area is becoming a platform of power competition between China, the Philippines, Vietnam, Malaysia, and Brunei. Five parties mentioned above are competing over sovereignty in certain areas of the SCS. SCS area became interesting to certain parties, considering its strategic value for expansive policy. In the contemporary era, the rise of this conflict perceived as a problem which caused by shifting balance of power, that happened when the U.S. sought to preserve its unilateral moment after the end of cold war. This lead to vacuum of power situation in the Southeast Asia, thus encourage China to build up presence in the dispute area. Even though there are only four ASEAN countries that directly involved, however the adoption of the Declaration on the SCS by all ASEAN member countries, asserted that in this case ASEAN is standing together to show their objections of China’s aggressiveness. With structural realism perspective as the analysis tool, tendencies of ASEAN member states’ different strategies are understandable by the explanation about motives behind it. Which Philippines and Vietnam tend to leaning towards balancing strategy against China. Cambodia, Laos, and Myanmar indicate towards bandwagoning strategy with China, while the rest of the members did not show tendencies of leaning either ways.